Development of Alcohol Detection with Ignition Lock System for Vehicles - Rafidi, Muhammad Nabil Annuar; Nik Ismail, Nik Mohd Asri (Evolution in Electrical and Electronic Engineering, 2021)
There are so many cases of accidents involving the drunk driver recently. In the current situation, the detection of a drunk driver is based on roadblock and it is not relevant for detecting a drunk driver. Due to the problem, this project will help to decrease the cases of the drunk driving issue. An alcohol detection system with an ignition lock for vehicles is one of the solutions for the drunk driver issue. The system includes the algorithms that sense the alcohol by using MQ-3 sensor for detection of the alcohol. The system equipped with components including MQ-3 sensor, Arduino Mega 2560, LCD display, Red LED and DC motor for detecting the presence of alcohol in a vehicle. The prescribed limit of this system is 39 mg/L. Once the system is turned on, the sensor will sense the alcohol vapor by doing the experiment that using alcohol beverage and non-alcohol beverages. There are two types of conditions for this system. First of all, when the sensor is detecting the level of alcohol is under the prescribed limit, the ignition lock will turn on, and then the DC motor will works like normal. Next, the sensor is detecting the level of alcohol is over the prescribed limit and thus the DC motor will stop functioning and the ignition lock will be off and thus the car will not moving. As for results, the system functions as it was programmed, but unfortunately, the sensor of the MQ-3 sensor does not function well due to the error in detecting alcohol even though the sensor has been calibrated. Hopefully, this system can be used in the future by adding some features for notifications to the authorities and reducing cases, including drunk drivers.